The impact of social studies teachers’ use of e-learning techniques to develop student’s perceived self-efficacy - Al-Hawamdeh, Basma Mohammad; Abu Alkishek, Israa Omar; Zureigat, Haitham Mohammad Ali (Institute of Advanced Engineering and Science, 2024)
Private universities in Jordan have witnessed a major shift in teaching methods and strategies, as e-learning techniques have become an integral part of the educational policies followed. Therefore, the study aimed to identify the effect of social studies teachers’ use of e-learning techniques in developing the perceived self-competencies of university students, depending on gender and field of specialization. To achieve this, the descriptive analytical method was used in conducting the study. The perceived self-efficacy test was applied to a sample of 292 university students who were randomly selected. The study found that e-learning techniques contributed to raising the level of perceived self-efficacy among males more than among females. It did not have a significant impact on its interaction with the student’s field of specialization. The results also indicate the importance of the role played by social studies teachers with technological educational techniques in improving the level of students’ self-efficacy. Moreover, social relations are among the most important factors contributing to building a conscious generation that preserves human dignity. Therefore, we must research the negatives of e learning to find out the reason behind the lack of improvement in the level of perceived self-efficacy among females.